Sociodemographic, psychosocial and clinical factors associated with uptake of genetic counselling for hereditary cancer: a systematic review. Issue 2 (23rd October 2016) - Willis, A.M.; Smith, S.K.; Meiser, B.; Ballinger, M.L.; Thomas, D.M.; Young, M.‐A.
Abstract : Evidence suggests that a significant proportion of individuals referred to cancer genetic counselling (GC) do not attend, and thus may not be engaged in adequate cancer risk management. We aimed to review the literature to better understand barriers to accessing GC and how they may be overcome. We conducted a systematic literature search for articles examining factors influencing cancer GC uptake as well as motivators and barriers to GC attendance. Factors were categorised as sociodemographic, psychosocial or clinical. The literature search identified 1413 citations, 35 of which met the inclusion criteria. GC uptake ranged from 19% to 88%. With the exceptions of education level, socioeconomic status, cancer‐specific distress, personal cancer diagnosis and actual and perceived risk of cancer, support was lacking for most sociodemographic, clinical and psychosocial factors as predictors of GC uptake. Cost and logistical barriers, emotional concerns, family concerns and low perceived personal relevance were reported as important considerations for those declining GC. We conclude that there is poor understanding of GC and a lack of decision support among those referred to GC. Research into ways of providing education and support to referred individuals will be important as the scope and availability of GC and genetic testing broaden. Abstract :